The Effect of Pelvic Rocking on The Level of Readiness of Pregnant Women in Facing Labour - Hardjanti, Triana Sri; Suwanti, Suwanti; Nurakhsin, Luthfiati Lathifah (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2025)
This study aims to determine the effect of pelvic rocking exercises on the level of readiness of pregnant women in facing labor. The research utilized a one-group pretest-posttest design. A sample of 30 pregnant women in their third trimester participated in the study. Before the intervention, a readiness assessment was conducted to measure the level of preparedness of the participants for labor. Following the pretest, pelvic rocking exercises were implemented for a period of two weeks. Afterward, a posttest was conducted to reassess the level of readiness. Data were analyzed using paired t-test to compare pre and post-intervention readiness scores. The results indicated a significant increase in the readiness level of pregnant women post-intervention (p 0.05). This suggests that pelvic rocking exercises may enhance the physical and psychological readiness of pregnant women in preparing for labor. Based on these findings, it is recommended that pelvic rocking exercises be considered as a beneficial intervention in antenatal care programs to support pregnant women in their labor preparation.